2021
DOI: 10.3389/fonc.2021.794399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relevance of the Ultrasonographic Features of Papillary Thyroid Carcinoma and Cervical Lymph Node Metastasis on Conventional and Contrast-Enhanced Ultrasonography

Abstract: BackgroundPreoperative prediction of lymph node metastases has a major impact on prognosis and recurrence for patients with papillary thyroid carcinoma (PTC). Thyroid ultrasonography is the preferred inspection to guide the appropriate diagnostic procedure.PurposeTo investigate the relationship between PTC and cervical lymph node metastasis (CLNM, including central and lateral LNM) using both conventional ultrasound (US) and contrast-enhanced ultrasound (CEUS).Material and MethodsOur study retrospectively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
13
2
Order By: Relevance
“…In this study, multifocality was an independent risk factor for predicting CLNM in PTC patients (p = 0.001), which is consistent with a previous study. The OR value of multifocality (OR = 5.274) in this study was significantly higher than previous studies (OR = 1.297-3.235) (14,18,24). The ill-defined, lobulated, or irregular margin of thyroid nodules is generally associated with the irregular growth of the fibrous stroma surrounding the PTC nodules or carcinoma invasion of the surrounding thyroid parenchyma.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In this study, multifocality was an independent risk factor for predicting CLNM in PTC patients (p = 0.001), which is consistent with a previous study. The OR value of multifocality (OR = 5.274) in this study was significantly higher than previous studies (OR = 1.297-3.235) (14,18,24). The ill-defined, lobulated, or irregular margin of thyroid nodules is generally associated with the irregular growth of the fibrous stroma surrounding the PTC nodules or carcinoma invasion of the surrounding thyroid parenchyma.…”
Section: Discussioncontrasting
confidence: 75%
“…Recently, CEUS has been widely used in differentiating between benign and malignant thyroid nodules and is a promising noninvasive method in the diagnosis of thyroid nodules (11). Several studies have reported that CEUS is useful for the evaluation of biological behavior and CLNM (12)(13)(14), but the enhancement patterns in different studies were inconsistent; thus, it is important to conduct further studies.…”
Section: Introductionmentioning
confidence: 99%
“…LNM had a close correlation with an unfavorable prognosis of thyroid cancer. [ 7 ] Some clinical characteristics such as age, gender, and tumor size were identified as biomarkers for predicting LNM, but their functions are limited. [ 34 ] Besides, the alterations of genes including BRAF and TERT have been proved to be associated with LNM, but with contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate prediction of LNM is essential in selecting appropriate treatment methods, improving curative effects, and prolonging the survival time of patients. [ 7 ] Although ultrasound is a convenient and effective method for thyroid disease screening, the efficacy of LNM detection by ultrasound is not ideal and occult LNM might be missed. [ 8 10 ] Therefore, it is of great importance to identify new biomarkers for assisting the LNM prediction and improving THCA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients can be cured by almost all thyroidectomy and neck lymph node dissection, and 131 I is used for postoperative ablation of occult microlesions. However, there are still 15-30% of patients with local recurrence and cervical lymph node metastasis (LNM) (1)(2)(3). More than 96% of potential driver mutations in PTC have been identified, which can lead to special histological features or biological behavior (4).…”
Section: Introductionmentioning
confidence: 99%